A Burkholderia thailandensis DedA Family Membrane Protein Is Required for Proton Motive Force Dependent Lipid A Modification - Panta, Pradip R.; Doerrler, William T. (Frontiers in Microbiology, 2021)
The DedA family is a conserved membrane protein family found in most organisms. A Burkholderia thailandensis DedA family protein, named DbcA, is required for high-level colistin (polymyxin E) resistance, but the mechanism awaits elucidation. Modification of lipopolysaccharide lipid A with the cationic sugar aminoarabinose (Ara4N) is required for colistin resistance and is dependent upon protonmotive force (PMF) dependent transporters. B. thailandensis ∆dbcA lipid A contains only small amounts of Ara4N, likely leading to colistin sensitivity. Two B. thailandensis operons are required for lipid A modification with Ara4N, one needed for biosynthesis of undecaprenyl-P-Ara4N and one for transport of the lipid linked sugar and subsequent lipid A modification. Here, we directed overexpression of each arn operon by genomic insertion of inducible promoters. We found that overexpression of arn operons in ∆dbcA can partially, but not completely, restore Ara4N modification of lipid A and colistin resistance. Artificially increasing the PMF by lowering the pH of the growth media also increased membrane potential, amounts of Ara4N, and colistin resistance of ∆dbcA. In addition, the products of arn operons are essential for acid tolerance, suggesting a physiological function of Ara4N modification. Finally, we show that ∆dbcA is sensitive to bacitracin and expression of a B. thailandensis UppP/BacA homolog (BTH_I1512) can partially restore resistance to bacitracin. Expression of a different UppP/BacA homolog (BTH_I2750) can partially restore colistin resistance, without changing the lipid A profile. This work suggests that maintaining optimal membrane potential at slightly alkaline pH media by DbcA is responsible for proper modification of lipid A by Ara4N and provides evidence of lipid A modification-dependent and -independent mechanisms of colistin resistance in B. thailandensis.